2020
DOI: 10.26656/fr.2017.4(4).077
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and quality evaluation of instant mango drink powder

Abstract: The study was conducted to develop a healthy instant mango drink powder and to compare its nutritional facts with commercially available mango drink powder. For this purpose, ripe Amropali mangoes were collected from a local source. After drying the mango pulp in a cabinet dryer, three formulations were prepared to compare with a locally available commercial brand mango drink powder. In this study, moisture, ash, protein, fat, carbohydrate, and energy contents were ranged from 0.2 to 4.6%, 0.4 to 2.6%, 0.7 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
2
1
1
Order By: Relevance
“…The study also revealed that the moisture content of FB2 beverage was significantly increased with higher proportions of F. deltoidea leaves as compared to NBR and FB1. This data was in accordance with the previous study by 43 on the instant Sorrel (Zobo) drinks and 44 on the instant mango drink powder. It has been demonstrated that the moisture content below 14% help in preventing bacterial, fungal, and yeast growth.…”
Section: Discussionsupporting
confidence: 93%
“…The study also revealed that the moisture content of FB2 beverage was significantly increased with higher proportions of F. deltoidea leaves as compared to NBR and FB1. This data was in accordance with the previous study by 43 on the instant Sorrel (Zobo) drinks and 44 on the instant mango drink powder. It has been demonstrated that the moisture content below 14% help in preventing bacterial, fungal, and yeast growth.…”
Section: Discussionsupporting
confidence: 93%
“…prepared instant beverage powder from extruded malted pearl millet (Babla) reported the antioxidant capacity as 1.78 μmole TE/g. The results of antioxidant capacity were close agreement withAkther et al (2020) for instant mango drink powder.…”
supporting
confidence: 76%
“…The results of anthocyanin content showed that the anthocyanin content of samples was significantly different (p<0.05). The anthocyanin content of the instant mango drinks powder was higher than reported by Akther et al (2020) for instant mango drink powder.…”
Section: Bioactive Compounds Of Instant Mango Drinks Powdercontrasting
confidence: 63%
“…Sensory parameters were appearance, color, texture, flavor, taste, and overall acceptability were evaluated. The scale was arranged from 1 to 9, the highest score (9) was assigned to the most preferred characteristic and the least score (1) to the least desired characteristic (Akther et al, 2020; Azab et al, 2019).…”
Section: Methodsmentioning
confidence: 99%